Comparison of the Independence Learning of Prospective Teacher through the Use of E-Learning during the Covid-19 Pandemic - Hermansyah Hermansyah; Eryuni Ramdhayani; Nurhairunnisah Nurhairunnisah; Erma Suryani; Sri Sugiarto (Postgraduate, University of Mataram, 2021)
The current learning process is carried out online with the help of e-learning. This certainly changes the pattern of learning and this pattern requires students to be more independent in the learning process. This study aims to compare the effect of using e-learning on the learning independence of prospective teachers in the exact field of exact sciences with the social and humanities field at Universitas Samawa. Respondents in this study amounted to 62 students from five study programs under the auspices of the Faculty of Teacher Training and Education. Respondents were divided into two based on the specifications of the fields of science, exact sciences, and social humanities. The data collection technique used observation technique with the tool used in the form of a Likert scale questionnaire. The results showed that in general, student-teacher candidates in the field of social humanities obtained a higher score of learning independence than prospective students in the field of exact sciences, while based on each indicator of learning independence, prospective students in the field of exact sciences teachers were higher than prospective students in the field of social humanities specifically on disciplinary indicators. The results of the influence test show that the significant value is greater than 0.05. So, it can be concluded that the use of e-learning during the covid-19 pandemic does not significantly affect the learning independence of prospective teacher students at Universitas Samawa